To simplify the expression 2(3x+4)−3(2x−2)+8(x−5), we can distribute the coefficients to the terms within the parentheses and then simplify by combining like terms.
Distributing the coefficients:
2(3x+4) = 6x + 8
3(2x−2) = 6x - 6
8(x−5) = 8x - 40
Simplifying the expression by combining like terms:
(6x + 8) - (6x - 6) + (8x - 40)
= 6x + 8 - 6x + 6 + 8x - 40
= (6x - 6x + 8x) + (8 + 6 - 40)
= 8x - 26
Therefore, the simplified expression is 8x - 26.
Simplify the expression.
2(3x+4)−3(2x−2)+8(x−5)
(1 point)
Responses
20x−26
20 x minus 26
8x−38
8 x minus 38
8x−26
8 x minus 26
20x+54
1 answer